BILATERAL SECONDARY SPONTANEOUS PNEUMOTHORAX IN A CHILD WITH PULMONARY TUBERCULOSIS - DR.DIVYA. S,; DR.A THUMJAA,; DR .DEEPAK KUMAR.P, (International Journal of Pharma and Bio Sciences, 2015)
A 14 year old girl presented with breathlessness and chest pain for three days, who is a known case of pulmonary tuberculosis on antituberculous drugs for past one month. Chest X –ray showed pneumothorax along the right lateral chest wall with lung margin seen medially with small pneumothorax seen in left upper zone. She was treated with intercostal tube drainage on right side chest wall for one week and continued with antituberculous treatment. After one week she recovered with no further episodes of pneumothorax.